2014
DOI: 10.1371/journal.pone.0108114
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Effective Collaborative Care for Treatment of Depression: A Systematic Review and Meta-Regression of 74 Randomised Controlled Trials

Abstract: BackgroundCollaborative care is a complex intervention based on chronic disease management models and is effective in the management of depression. However, there is still uncertainty about which components of collaborative care are effective. We used meta-regression to identify factors in collaborative care associated with improvement in patient outcomes (depressive symptoms) and the process of care (use of anti-depressant medication).Methods and FindingsSystematic review with meta-regression. The Cochrane Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
144
2
14

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(170 citation statements)
references
References 51 publications
4
144
2
14
Order By: Relevance
“…We found that studies performed in the US had a greater effect size compared to European studies, which is in contrast with previous findings [25]. The US studies were also considerably more homogeneous than the European studies, which may be related to similarities and differences in healthcare systems between the US and Europe [16].…”
Section: Comparison With the Literaturecontrasting
confidence: 99%
“…We found that studies performed in the US had a greater effect size compared to European studies, which is in contrast with previous findings [25]. The US studies were also considerably more homogeneous than the European studies, which may be related to similarities and differences in healthcare systems between the US and Europe [16].…”
Section: Comparison With the Literaturecontrasting
confidence: 99%
“…Our observed effect size was less than that used to power the study, although the 95% CI around it (0.26, 95% CI 0.07 to 0.46) encompassed our original target (0.4). Our result also lies within the 95% CI of the SMD found in the most recent meta-analysis of collaborative care, 73 which includes our results (overall SMD 0.28, 95% CI 0.23 to 0.33), and is no different from US (SMD 0.28, 95% CI 0.21 to 0.35), non-US excluding the UK (SMD 0.36, 95% CI 0.13 to 0.59), and other UK (SMD 0.32, 95% CI 0.07 to 0.57) trials. 23 Collaborative care is as effective in the UK health-care system, an example of an integrated health system with a well-developed primary care sector, as in the USA.…”
Section: Clinical Outcomessupporting
confidence: 89%
“…69,70 The incorporation of collaborative care for depression in adults has been shown to provide added value for the treatment of depression in adults over and above psychological and/or medication treatments. 71,72 The BPI treatment manualised for this study emerged from the treatment as usual in ADAPT. The intervention is a treatment based on restructuring and codification of the principles and practices found in the domains of skilled assessment, listening, information-giving, advising, problem-solving, safety, caring and explaining about adolescent depression.…”
mentioning
confidence: 99%